(untitled) - Věra Hellerová; Valérie Tóthová; Inka Kratochvílová; Martin Červený; Lukáš Novotný; Andrej Tóth (University of Ostrava, 2023)
Aim: The period after the First World War was very challenging for countries across the whole of Europe. The health condition and health literacy of inhabitants in the First Czechoslovak Republic were poor. Design: Historical research. Methods: Direct, indirect, and progressive methods were chosen to describe community care and public health care. Archival sources were found in selected archives in the Czech and Slovak republics. Results: It is evident that many changes related to preventing infectious and non-infectious diseases. Ethnic and socioeconomic diversity was a factor that influenced the health condition and knowledge of the population, and the success of preventive measures. Therefore, the involvement of professional and voluntary organizations, and government institutions was essential. Public health care arose from the idea that a healthy population was the basis of the newly-formed republic. Conclusion: The literature and archival sources discovered show the importance of the health condition of the population to the newly-formed Czechoslovak state. To improve the health condition of the population, interventions were realized in cooperation with various organizations. Concurrently, there was an appreciable effort to enhance the health literacy of the population.